Infundebulectomy in management of uterine artery or uterine wall injury during complicated and difficult caesarean section: case series study - Mitwally, Abo B. A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
It is case series trying to save uterus in situation where one site of it is severely injured or in severe uncontrollable bleeding in one of the uterine arteries either during control of massive hemorrhage associated with friable tissues with severe adhesion, some cases of placenta accrete spectrum, some cases of uterine rupture and in caesarean section myomectomy.